Negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery
By using the silicon nanofiber/carbon nanotube composite material prepared by electrospinning as the negative electrode material in the lithium-ion battery, the problem of volume expansion of the negative electrode material during the process of deintercalating lithium in the existing technology is solved, and a higher capacity is achieved. Retention and cycling performance.
Patent Information
- Application Number
- CN202411320615.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-17
AI Technical Summary
The existing silicon carbon negative electrode materials will cause irreversible volume expansion during the deintercalation of lithium, resulting in damage to the electrode structure and falling off the active material, affecting the expansion and cycling performance of the battery cell.
A negative electrode material is used, which includes a first active material (silicon nanofiber) and a second active material (carbon nanotube), prepared by a coaxial electrospinning method. The silicon nanofiber is located inside the carbon nanotube, and the outer layer of carbon nanotube is The tube limits the volume expansion of the silicon fiber.
It effectively reduces the expansion rate of the negative electrode material, increases the capacity retention rate of the battery, improves the battery cycle performance, increases the transmission rate of lithium ions, and improves the charging capacity of the battery core.
Smart Images

Figure CN119324209A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode material and a preparation method thereof, a negative electrode sheet and a lithium ion battery. Background Art
[0002] At present, the negative electrode material of lithium-ion batteries mainly uses traditional graphite materials. However, due to its significant specific capacity advantage, silicon-based materials are gradually increasing their proportion in negative electrode materials. Silicon-based negative electrode materials are mainly divided into two technical routes: silicon-oxygen and silicon-carbon. Among them, silicon-carbon negative electrode materials are nano-silicon and graphite. This material utilizes the high specific capacity characteristics of nano-silicon, and at the same time, through the reaction with graphite, it can alleviate the volume change of silicon during the charge and discharge process to a certain extent, and improve the structural stability and cycle performance of the material.
[0003] The silicon-carbon materials prepared by the prior art will cause irreversible volume expansion during the process of lithium insertion and extraction, resulting in the destruction of the electrode structure and the shedding of active materials, thereby affecting the expansion and cycle performance of the battery cell. In view of this, it is urgent to develop a negative electrode material that can effectively reduce the expansion rate of the negative electrode material while improving the capacity retention rate of the battery. Summary of the invention
[0004] The purpose of the present invention is to provide a negative electrode material to address the deficiencies of the prior art, which can effectively reduce the expansion rate of the negative electrode material and improve the capacity retention rate of the battery.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A negative electrode material includes a first active material and a second active material, wherein the first active material is in a linear structure, the second active material is in a tubular structure, the first active material is located inside the second active material, the first active material is silicon nanofiber, and the second active material is carbon nanotube.
[0007] Preferably, the diameter Q1 of the silicon nanofiber is 20-30 nm.
[0008] Preferably, the inner diameter Q2 of the carbon nanotube is 60-96 nm.
[0009] Preferably, the diameter Q1 of the silicon nanofiber and the inner diameter Q2 of the carbon nanotube satisfy the relationship: 3.0≤Q2 / Q1≤3.2.
[0010] Preferably, the outer diameter Q3 of the carbon nanotube is 84-139 nm.
[0011] Preferably, the inner diameter Q2 of the carbon nanotube and the outer diameter Q3 of the carbon nanotube satisfy the relationship: 1.4≤Q3 / Q2≤1.45.
[0012] Preferably, the mass ratio of the silicon nanofibers to the carbon nanotubes is 30%-50%. In addition, the present invention also provides a method for preparing a negative electrode material, comprising the following steps:
[0013] S1, preparing a first precursor solution by mixing nano silicon particles, an organic solvent and an excipient;
[0014] S2, preparing a second precursor solution by mixing a monomer organic substance, an organic solvent and an excipient;
[0015] S3, placing the first precursor solution and the second precursor solution into different coaxially arranged syringes, respectively, and performing electrospinning to obtain a uniform nanofiber composite;
[0016] S4, placing the nanofiber composite in a reaction device protected by an inert gas and calcining it to obtain the negative electrode material.
[0017] Preferably, in step S1 and step S2, the excipient is any one of polyvinyl pyrrolidone, polyacrylonitrile, polypropylene alcohol, polyethylene glycol and chitosan.
[0018] Preferably, in step S3, the voltage during electrospinning is 18-20 kV.
[0019] Preferably, in step S4, the calcination temperature is 200-300° C., and the calcination time is 18-28 hours.
[0020] In addition, the present invention also provides a negative electrode sheet, comprising the above-mentioned negative electrode material.
[0021] In addition, the present invention also provides a lithium-ion battery, including a battery core wound by a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell encapsulating the battery core and the electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.
[0022] Compared with the prior art, the beneficial effect of the present invention is that the present invention prepares the negative electrode material through a coaxial electrospinning method. The core of the negative electrode material is silicon nanofiber, and the coating layer is carbon nanotube. The outer layer of carbon nanotube can limit the volume expansion of the silicon fiber, which can improve the battery cycle performance while having a higher specific surface area, exposing more reaction active sites, thereby improving the transmission rate of lithium ions and improving the charging capacity of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the structure of the negative electrode material according to one embodiment of the present invention.
[0024] Among them, 1-first active material; 2-second active material. DETAILED DESCRIPTION
[0025] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] According to the first aspect of the present application, the present application provides a negative electrode material, including a first active material and a second active material, wherein the first active material is in a linear structure, the second active material is in a tubular structure, the first active material is located inside the second active material, the first active material is silicon nanofiber, and the second active material is carbon nanotube. The outer carbon nanotube can limit the volume expansion of the silicon fiber, improve the battery cycle performance, and have a higher specific surface area, exposing more reactive sites, thereby increasing the transmission rate of lithium ions and improving the charging capacity of the battery cell.
[0027] In some embodiments, the diameter Q1 of the silicon nanofiber is 20-30nm, for example, it can be 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm. Among them, when the diameter of the silicon nanofiber is less than 20nm, it is difficult to exist stably in the tube-in-wire structure, which is easy to cause the breakage of the silicon nanofiber and thus cause the collapse of the composite tube-in-wire structure, which does not improve the expansion and may even deteriorate the k value; when the diameter of the silicon nanofiber is greater than 30nm, on the one hand, it is difficult to ensure the relationship with the inner diameter of the carbon nanotube, resulting in unsatisfactory effect of improving the expansion, and on the other hand, it will lose the significance of the nano-scale silicon material, which provides a larger space to cope with volume strain. In some embodiments, the inner diameter Q2 of the carbon nanotube is 60-96nm, for example, it can be 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 96nm. The inner diameter of carbon nanotubes is mainly limited by the diameter of silicon nanofibers. When it is less than the lower limit, the space between the tube and the wire may not be enough to accommodate the volume strain of silicon. When it is greater than the upper limit, the excessive space between the tube and the wire causes ED loss. On the other hand, it is easy to be crushed during rolling, resulting in the collapse of the tube-wire structure, thereby failing to improve the performance of the negative electrode material.
[0028] In some embodiments, the diameter Q1 of the silicon nanofiber and the inner diameter Q2 of the carbon nanotube satisfy the relationship: 3.0≤Q2 / Q1≤3.2, for example, 3.0, 3.1, 3.2. Limiting the value within the range can provide a buffer space when the silicon fiber reaches 300% volume expansion during charging, ensure the structural stability of the negative electrode material, thereby ensuring the stability of the negative electrode structure and improving the service life of the battery.
[0029] The outer diameter Q3 of the carbon nanotube is 84-139nm, for example, it can be 84nm, 90nm, 95nm, 100nm, 110nm, 120nm, 125nm, 130nm, 135nm, 139nm. When the outer diameter of the carbon nanotube is less than 84, the wall thickness of the carbon nanotube is too thin, which may not be enough to withstand the force in the subsequent processing rolling process, causing structural collapse and failure to improve expansion; when the outer diameter of the carbon nanotube is greater than 139, the wall of the carbon nanotube is too thick, making it more difficult for lithium ions to pass through when the battery is working, affecting the performance of the silicon nanofiber.
[0030] The inner diameter Q2 of the carbon nanotube and the outer diameter Q3 of the carbon nanotube satisfy the relationship: 1.4≤Q3 / Q2≤1.45, for example, it can be 1.4, 1.41, 1.42, 1.43, 1.44, 1.45. Limiting the value within the range can prevent the material from being pulverized and collapsed due to the nanotube wall being too thin, improve the stability of the material structure, and prevent the performance of the silicon material from being affected by the carbon nanotube wall being too thick.
[0031] The mass ratio of silicon nanofibers to carbon nanotubes is 30%-50%, for example, 30%, 35%, 40%, 45%, 50%. Silicon material has a high specific capacity, but its conductivity is weaker than carbon. Carbon nanotubes of sufficient mass can provide sufficient conductivity for the negative electrode material. Therefore, the appropriate content ratio of each component can ensure that the negative electrode material has a high conductivity while using silicon to increase the capacity of the negative electrode material, and effectively suppress the phenomenon of structural damage of the negative electrode material caused by the periodic stress generated by the volume change of silicon.
[0032] According to a second aspect of the present application, the present application provides a method for preparing a negative electrode material, comprising the following steps:
[0033] S1, preparing a first precursor solution by mixing nano silicon particles, an organic solvent and an excipient;
[0034] S2, preparing a second precursor solution by mixing a monomer organic substance, an organic solvent and an excipient;
[0035] S3, placing the first precursor solution and the second precursor solution into different coaxially arranged syringes, respectively, and performing electrospinning to obtain a uniform nanofiber composite;
[0036] S4, placing the nanofiber composite in a reaction device protected by an inert gas and calcining it to obtain the negative electrode material.
[0037] In some embodiments, in step S1 and step S2, the excipient is any one of polyvinyl pyrrolidone, polyacrylonitrile, polypropylene alcohol, polyethylene glycol and chitosan.
[0038] In some embodiments, in step S1, the monomer organic substance is selected from any one of graphite, ethylene, propylene, styrene and butadiene.
[0039] In some embodiments, in step S3, the syringe is connected to the positive pole of the power supply in a horizontal direction, and an aluminum foil is placed opposite the needle and connected to the negative pole of the power supply, and the distance between the needle and the aluminum foil is 15-20 cm.
[0040] In some embodiments, in step S3, the voltage during electrospinning is 18-20 kV, for example, 18 kV, 19 kV, 20 kV. The voltage affects the diameter of the electrospinning material. The greater the voltage, the smaller the diameter of the material; the smaller the voltage, the larger the diameter of the material; too low a voltage can easily lead to too thick walls of carbon nanotubes and too thick diameters of silicon nanofibers, making it difficult to obtain the inner diameter ratio parameters set in this application; when the voltage is too high, the spinning speed is relatively faster, and it is easy to obtain a broken, uneven surface, and negative electrode material that cannot fully form a tube-in-wire structure.
[0041] In some embodiments, in step S4, the calcination temperature is 200-300°C, for example, it can be 200°C, 220°C, 240°C, 260°C, 280°C, or 300°C; the calcination time is 18-28h, for example, it can be 18h, 20h, 22h, 24h, 26h, or 28h.
[0042] According to a third aspect of the present application, the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the above-mentioned negative electrode material.
[0043] According to the fourth aspect of the present application, the present application provides a lithium-ion battery, comprising a battery cell formed by winding a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell that encapsulates the battery cell and the electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.
[0044] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material may include but is not limited to a chemical formula such as Li a Ni x Co y M z O2-b N b (wherein 0.95≤a≤1.2, x>0, y≥0, z≥0, and x+y+z=1, 0≤b≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S) The positive electrode active material may also be, but is not limited to, LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5 O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2, etc. The positive active material may also be modified. The method of modifying the positive active material should be known to those skilled in the art. For example, the positive active material may be modified by coating, doping, etc. The material used for the modification may include but is not limited to a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc. The positive current collector is usually a structure or part for collecting current. The positive current collector may be various materials suitable for use as a positive current collector for lithium-ion batteries in the art. For example, the positive current collector may include but is not limited to metal foil, etc., and more specifically may include but is not limited to aluminum foil, etc.
[0045] The separator can be any material suitable for secondary battery separators in the art, for example, it can be a combination of one or more of, but not limited to, polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.
[0046] The lithium-ion battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.
[0047] The present invention will be described in further detail below in conjunction with specific implementation modes, but the implementation modes of the present invention are not limited thereto.
[0048] Example 1
[0049] Negative electrode material preparation:
[0050] like Figure 1 As shown, a negative electrode material provided in this embodiment includes a first active material 1 and a second active material 2, wherein the first active material 1 is in a linear structure, the second active material 2 is in a tubular structure, the first active material 1 is located inside the second active material 2, the first active material 1 is silicon nanofiber, and the second active material 2 is carbon nanotube.
[0051] The method for preparing the negative electrode material comprises the following steps:
[0052] S1, 0.5 g Si nanoparticles were uniformly dispersed in 5 mL N, N-dimethylformamide (DMF) and 2 g tetraethyl orthosilicate (TEOS) solvent, ultrasonically dispersed for 3 h, and then 1.4 g polyvinyl pyrrolidone (PVP) was added and stirred for 12 h to obtain the first precursor solution;
[0053] S2, dispersing 1.25 g of graphite powder into 5 ml of DMF and 2 g of TEOS, ultrasonically dispersing for 3 h, then adding 0.8 g of polyvinyl pyrrolidone (PVP) and stirring for 12 h to obtain a second precursor solution;
[0054] S3, respectively putting the first precursor solution and the second precursor solution into different syringes, connecting the syringes to coaxial needles, and coaxially electrospinning at a voltage of 20 kV and a spacing of 17.5 cm to obtain a nanofiber composite;
[0055] S4, heating to 250° C. in a tubular furnace for pre-oxidation for 2 h, and finally heating to 850° C. under argon gas protection for carbonization for 2 h to obtain the negative electrode material.
[0056] The diameter Q1 of the silicon nanofiber is 20 nm, the inner diameter Q2 of the carbon nanotube is 60 nm, the inner diameter Q3 of the carbon nanotube is 84 nm, and the mass ratio of the silicon nanofiber to the carbon nanotube is 40%.
[0057] Preparation of lithium-ion batteries:
[0058] 1) Positive electrode sheeting: The positive electrode material lithium cobalt oxide, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system at a mass ratio of 98:1.0:1.0, and then coated on Al foil. After drying, rolling, and slitting, the positive electrode sheet is obtained.
[0059] 2) Negative electrode sheeting: The negative electrode material, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system at a mass ratio of 97.85:0.6:0.8:0.75, and then coated on Cu foil. After drying, rolling, and slitting, the negative electrode sheet is obtained.
[0060] 3) Preparation of isolation membrane: A polyethylene (PE) porous polymer film is used as the isolation membrane.
[0061] 4) Preparation of electrolyte: A solution prepared by mixing lithium salt LiPF6 and a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP) = 26:26:16:32, mass ratio) in a mass ratio of 9:91 was used as the electrolyte of the lithium battery.
[0062] 5) Battery production: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play a role of safety isolation, and wind them to obtain an electrode assembly. Place the electrode assembly in a packaging shell, inject electrolyte and package it to obtain a lithium battery.
[0063] Example 2
[0064] Different from Example 1, in the negative electrode material of this example, the diameter Q1 of the silicon nanofiber is 25 nm, the inner diameter Q2 of the carbon nanotube is 79 nm, the carbon nanotube Q3 is 111 nm, and the mass ratio of the silicon nanofiber to the carbon nanotube is 40%.
[0065] The rest is the same as Example 1 and will not be described again here.
[0066] Example 3
[0067] Different from Example 1, in the negative electrode material of this example, the diameter Q1 of the silicon nanofiber is 30 nm, the inner diameter Q2 of the carbon nanotube is 92 nm, the carbon nanotube Q3 is 130 nm, and the mass ratio of the silicon nanofiber to the carbon nanotube is 40%.
[0068] The rest is the same as Example 1 and will not be described again here.
[0069] Example 4
[0070] Different from Example 1, in the negative electrode material of this example, the diameter Q1 of the silicon nanofiber is 20 nm, the inner diameter Q2 of the carbon nanotube is 60 nm, the carbon nanotube Q3 is 84 nm, and the mass ratio of the silicon nanofiber to the carbon nanotube is 30%.
[0071] The rest is the same as Example 1 and will not be described again here.
[0072] Example 5
[0073] Different from Example 1, in the negative electrode material of this example, the diameter Q1 of the silicon nanofiber is 20 nm, the inner diameter Q2 of the carbon nanotube is 60 nm, the carbon nanotube Q3 is 84 nm, and the mass ratio of the silicon nanofiber to the carbon nanotube is 50%.
[0074] The rest is the same as Example 1 and will not be described again.
[0075] Different from Example 1, in the negative electrode material of this comparative example, the diameter Q1 of the silicon nanofiber is 20 nm, the inner diameter Q2 of the carbon nanotube is 60 nm, the carbon nanotube Q3 is 84 nm, and the mass ratio of the silicon nanofiber to the carbon nanotube is 20%.
[0076] The rest is the same as Example 1 and will not be described again here.
[0077] Comparative Example 2
[0078] Different from Example 1, in the negative electrode material of this comparative example, the diameter Q1 of the silicon nanofiber is 20 nm, the inner diameter Q2 of the carbon nanotube is 60 nm, the carbon nanotube Q3 is 84 nm, and the mass ratio of the silicon nanofiber to the carbon nanotube is 60%.
[0079] The rest is the same as Example 1 and will not be described again here.
[0080] Comparative Example 3
[0081] Different from Example 1, the voltage of classical spinning in step S3 of preparing the negative electrode material of this comparative example is 15 kV. In the obtained negative electrode material, the diameter Q1 of silicon nanofiber is 35 nm, the inner diameter Q2 of carbon nanotube is 85 nm, the carbon nanotube Q3 is 140 nm, and the mass ratio of silicon nanofiber to carbon nanotube is 40%.
[0082] The rest is the same as that of Example 1 and will not be described again here.
[0083] Comparative Example 4
[0084] Different from Example 1, the voltage of classical spinning in step S3 of preparing the negative electrode material of this comparative example is 23 kV. In the obtained negative electrode material, the diameter Q1 of silicon nanofiber is 15 nm, the inner diameter Q2 of carbon nanotube is 35 nm, the carbon nanotube Q3 is 55 nm, and the mass ratio of silicon nanofiber to carbon nanotube is 40%.
[0085] The rest is the same as that of Example 1 and will not be described again here.
[0086] Comparative Example 5
[0087] Different from Example 1, the negative electrode material of this comparative example only contains carbon nanotube material.
[0088] The rest is the same as that of Example 1 and will not be described again here.
[0089] Comparative Example 6
[0090] Different from Example 1, the negative electrode material of this comparative example only contains silicon nanofiber material.
[0091] The rest is the same as that of Example 1 and will not be described again here.
[0092] Comparative Example 7
[0093] Different from Example 1, the negative electrode material of this comparative example is a conventional silicon-carbon coated material, that is, the core is silicon particles and the shell is a carbon coating layer.
[0094] The rest is the same as that of Example 1 and will not be described again here.
[0095] The parameters of the negative electrode materials in Comparative Examples 1-4 and Examples 1-7 are shown in Table 1 below.
[0096] Table 1
[0097]
[0098]
[0099] Performance Testing
[0100] Take 5 lithium batteries prepared in the comparative example and the example, respectively, and repeatedly charge and discharge the lithium batteries in an environment of 25° C. through the following steps, and calculate the cycle capacity retention rate and thickness expansion rate of the batteries.
[0101] 1. Thickness expansion rate test:
[0102] First, in an environment of 25°C, the first charge and discharge were performed, constant current and constant voltage charging was performed at a charging current of 0.5C until the upper limit voltage was 4.53V, and then constant current discharge was performed at a discharge current of 0.7C until the final voltage was 3V, and then 300 charge and discharge cycles were performed, and the thickness of the initial and 300th cycles was recorded. Thickness change rate = (thickness after 300 cycles - initial thickness) / initial thickness × 100%.
[0103] 2. Capacity retention rate test:
[0104] First, in an environment of 25°C, the first charge and discharge were performed, constant current and constant voltage charging was performed at a charging current of 0.5C until the upper limit voltage was 4.53V, and then constant current discharge was performed at a discharge current of 0.7C until the final voltage was 3V, and the discharge capacity of the first cycle was recorded, and then 300 charge and discharge cycles were performed, and the discharge capacity of the 300th cycle was recorded. Capacity retention rate = capacity after 300 cycles / initial capacity × 100%.
[0105] The lithium ion batteries prepared in the embodiment and the comparative example were respectively subjected to electrochemical performance tests. The test results are shown in Table 2.
[0106] Table 2
[0107]
[0108]
[0109] From the comparison of the experimental data of Examples 1-5 and Comparative Examples 1-7 in Table 2, it can be seen that the expansion rate and capacity retention rate of the lithium battery prepared by the negative electrode material obtained by coaxial electrospinning in the present application after 300cls of normal temperature cycling are greatly improved. The volume expansion of this type of negative electrode material is very small, which effectively improves the stability of the interface and the cycle life of the battery.
[0110] From the data comparison of Example 1 and Comparative Examples 1-2, it can be seen that when the ratio of silicon nanofiber to carbon nanotube fiber is within the set range, the thickness expansion rate and capacity retention rate of the battery are excellent. When the ratio of silicon nanofiber to carbon nanotube fiber is less than the set range, the space between the tube and the wire is not enough to accommodate the expansion of silicon during the cycle, thereby causing the material to rupture and affecting the life of the battery; when the ratio of silicon nanofiber to carbon nanotube fiber is greater than the set range, the excessive space between the tube and the wire causes the loss of ED, and on the other hand, it is easy to crush during rolling, resulting in the collapse of the tube-wire structure, thereby failing to improve the performance of the negative electrode material.
[0111] From the data comparison of Examples 1-3 and Comparative Examples 3-4, it can be seen that when the data of Q2 / Q1 and Q3 / Q2 are both within the set range, the battery prepared by the negative electrode material provided by the present application has a small thickness expansion rate and a high capacity retention rate. When Q2 / Q1 is less than the set range, the wall thickness of the nanotube is too thin and may not be enough to withstand the force in the subsequent processing rolling process, causing structural collapse and failure to improve expansion. When Q3 / Q2 is greater than the set range, the wall of the carbon nanotube is too thick, making it more difficult for lithium ions to pass through when the battery is working, affecting the performance of the silicon nanofiber.
[0112] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A negative electrode material, characterized in that: It includes a first active material and a second active material, the first active material is in a linear structure, the second active material is in a tubular structure, the first active material is located inside the second active material, the first active material is silicon nanofiber, and the second active material is carbon nanotube.
2. A negative electrode material according to claim 1, characterized in that: The diameter Q1 of the silicon nanofiber is 20-30 nm.
3. A negative electrode material according to claim 1, characterized in that: The inner diameter Q2 of the carbon nanotube is 60-96 nm.
4. A negative electrode material according to claim 1, characterized in that: The diameter Q1 of the silicon nanofiber and the inner diameter Q2 of the carbon nanotube satisfy the relationship: 3.0≤Q2 / Q1≤3.
2.
5. A negative electrode material according to claim 1, characterized in that: The outer diameter Q3 of the carbon nanotube is 84-139 nm.
6. A negative electrode material according to claim 5, characterized in that: The inner diameter Q2 of the carbon nanotube and the outer diameter Q3 of the carbon nanotube satisfy the relationship: 1.4≤Q3 / Q2≤1.
45.
7. A negative electrode material according to claim 1, characterized in that: The mass ratio of the silicon nanofibers to the carbon nanotubes is 30%-50%.
8. A method for preparing a negative electrode material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, preparing a first precursor solution by mixing nano silicon particles, an organic solvent and an excipient; S2, preparing a second precursor solution by mixing a monomer organic substance, an organic solvent and an excipient; S3, placing the first precursor solution and the second precursor solution into different coaxially arranged syringes, respectively, and performing electrospinning to obtain a uniform nanofiber composite; S4, placing the nanofiber composite in a reaction device protected by an inert gas and calcining it to obtain the negative electrode material.
9. The method for preparing the negative electrode material according to claim 8, characterized in that: In step S1 and step S2, the excipient is any one of polyvinyl pyrrolidone, polyacrylonitrile, polypropylene alcohol, polyethylene glycol and chitosan.
10. The method for preparing the negative electrode material according to claim 8, characterized in that: In step S3, the voltage during electrospinning is 18-20 kV.
11. The method for preparing the negative electrode material according to claim 8, characterized in that: In step S4, the calcination temperature is 200-300° C., and the calcination time is 18-28 hours.
12. A negative electrode sheet, characterized in that: The negative electrode material comprises the negative electrode material according to any one of claims 1 to 7.
13. A lithium ion battery, characterized in that: Including the negative electrode sheet as claimed in claim 12.
Citation Information
Patent Citations
Silicon-based negative electrode material and method thereof
CN104112847A
Preparation method of nanometer silicon-carbon composite negative electrode material for lithium ion battery
CN108923035A
Silicon-carbon negative electrode material with tubular-linear structure and preparation method thereof
CN112242513A
Hollow carbon fiber material as well as preparation method and application thereof
CN115074869A
Lithium ion battery silicon carbon nanowire material and preparation method and application thereof
CN115394980A